Cellular and molecular mechanisms of immunomodulation in the brain through environmental enrichment - Singhal, Gaurav; Jaehne, Emily J.; Corrigan, Frances; Baune, Bernhard T. (Frontiers in Cellular Neuroscience, 2014)
Recent studies on environmental enrichment (EE) have shown cytokines, cellular immune components (e.g. T lymphocytes, NK cells) and glial cells in causal relationship to EE in bringing out changes to neurobiology and behavior. The purpose of this review is to evaluate these neuroimmune mechanisms associated with neurobiological and behavioral changes in response to different EE methods. We systematically reviewed common research databases. After applying all inclusion and exclusion criteria, 328 articles remained for this review. Physical exercise, a form of EE, elicits anti-inflammatory and neuromodulatory effects through interaction with several immune pathways including IL-6 secretion from muscle fibers, reduced expression of TLR’s on monocytes and macrophages, reduced secretion of adipokines, modulation of hippocampal T cells, priming of microglia and upregulation of MKP-1 in CNS. In contrast, immunomodulatory roles of other enrichment methods are not studied extensively. Nonetheless, studies showing reduction in the expression of IL-1β and TNF-α in response to enrichment with novel objects and accessories suggest anti-inflammatory effects of novel environment. Likewise, social enrichment, though considered a necessity for healthy behavior, results in immunosuppression in socially defeated animals. This has been attributed to reduction in T lymphocytes, NK cells and IL-10 in subordinate animals. EE through sensory stimuli has been investigated to a lesser extent and the effect on immune factors has not been evaluated yet. Discovery of this multidimensional relationship between immune system, brain functioning and EE has paved a way towards formulating environ-immuno therapies for treating psychiatric illnesses with minimal use of pharmacotherapy. While the immuno-modulatory role of physical exercise has been evaluated extensively, more research is required to investigate neuroimmune changes associated with other enrichment methods.